Prevalence of methicillin resistance and virulence determinants of Staphylococcus aureus in diabetic foot ulcers - Sandhu, Sumeet; Rathnayake, Irani Udeshika; Huygens, Flavia (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetic foot ulceration (DFU) is a multifactorial process and is responsible for considerable morbidity and contributes to the increasing cost of health care worldwide. The diagnosis and identification of these ulcers remains a complex problem. Bacterial infection is promoted in the diabetic foot wound by decreased vascular supply and impaired host immune response. As conventional clinical microbiological methods are time-consuming and only identifies about 1% of the wound microbiota, detection of bacteria present in DFUs using molecular methods is highly advantageous and efficient. The aim of this study was to assess the virulence and methicillin resistance profiles of Staphylococcus aureus detected in DFUs using DNA-based methods. Methods: A total of 223 swab samples were collected from 30 patients from March to October 2012. Bacterial DNA was extracted from the swab samples using standard procedures and was used to perform polymerase chain reaction (PCR) using specific oligonucleotide primers. The products were visualized using agarose gel electrophoresis. Results: S. aureus was detected in 44.8% of samples. 25% of the S. aureus was methicillin-resistant S. aureus harboring the mecA gene. The alpha-toxin gene was present in 85% of the S. aureus positive samples. 61% of the S. aureus present in DFU samples harbored the exfoliatin factor A gene. Both the fibronectin factor A and fibronectin factor B gene were detected in 71% and 74% of the S. aureus positive samples. Conclusions: DNA-based detection and characterization of bacteria in DFUs are rapid and efficient and can assist in accurate, targeted antibiotic therapy of DFU infections. The majority of S. aureus detected in this study were highly virulent and also resistant to methicillin. Further studies are required to understand the role of S. aureus in DFU trajectory.